Monitoring the impact of COVID-19 in Myanmar: Agricultural commodity traders - Late June 2020 survey round - Goeb, Joseph; Zu, A Myint; Synt, Nang Lun Kham; Zone, Phoo Pye; Boughton, Duncan; Maredia, Mywish K. (International Food Policy Research Institute, 2020)
Crop traders comprise the mid-stream of Myanmar’s food supply chain, forming important links between farms and food processors, exporters, commodity exchange centers, and urban food markets. Traders engage in a variety of business activities ranging from wholesalers that buy, store, grade, and sell commodities to brokers that facilitate crop sales on commissions. Many traders have strong and direct ties to farmers, often providing farmers with agricultural inputs on credit to strengthen relationships and to build business later in the year when crops are harvested and sold. These connections to the farm have important implications for any challenges that traders face due to the COVID-19 crisis. Effects on traders will also be felt upstream by farmers through both their post-harvest crop marketing activities, including the prices they receive for their crops, and potentially through access to agricultural inputs on credit. Furthermore, challenges to crop trading will also have effects on the food system downstream and, ultimately, on consumers. This is the second policy note in a series presenting results from phones surveys tracking a sample of crop traders across Myanmar. The surveys are designed to better understand the effects of COVID-19 shocks on Myanmar’s agri-food marketing system. This Policy Note builds on the results from the first round of the survey of crop traders. 1 This second round of the survey also added questions on two key themes from the first-round report – credit offered out by traders to farmers and trader’s use of mobile phones.